Assessment of green roofs in comparison to concrete roofs to mitigate heat on the urban surfaces of Kathmandu - Maharjan, Adarsha; Uprety, Sanjay; Bajracharya , Ashim Ratna (Journal of Innovations in Engineering Education, 2025)
This study examines how well green roofs perform thermally in comparison to concrete roofs and how they affect indoor room temperatures in urban settings. ICIMOD's Kailash Bhawan in Kathmandu valley is the site of the study, which uses temperature and relative humidity data gathered from both green and concrete roofs to reduce the effects of Urban Heat Island (UHI) and increase energy efficiency. The findings show that green roofs greatly reduce the impacts of UHI by lowering surface temperatures compared to concrete roofs by 32%. According to correlation studies, green roofs account for 45.9% of the fluctuation in interior room temperature, whilst concrete roofs' surface temperature accounts for 54%. In addition, the concrete roof accounts for 71% of the variance in the interior temperature in the absence of air conditioning, whereas the green roof accounts for 24.01%. According to these results, green roofs may help reduce energy use and improve thermal comfort. According to the study, installing green roofs in densely populated areas like Kathmandu is a sustainable way to reduce the effects of UHI and control internal temperatures, which will increase energy efficiency.